New nanostructured manganites of LaMeIICuZnMnO6 (MeII — Mg, Ca, Sr, Ba) - Kasenova, Sh.B.; Sagintaeva, Zh.I.; Kasenov, B.K.; Turtubaeva, M.O.; Nukhuly, А.; Kuanyshbekov, Ye.Ye.; Isabaeva, M.A. (KU Publ., 2021)
The copper-zinc manganites of LaMeIICuZnMnO6 (MeII — Mg, Ca, Sr, Ba) have been synthesized with the high-temperature interaction of alkaline earth metals carbonates with oxides of lanthanum (III), copper (II), zinc (II) and manganese (III). The synthesized polycrystalline copper-zinc manganites have been grinded on the Retsch vibration mill MM301 (Germany). As a result their nanostructured particles have been obtained. Their sizes have been determined using an electron microscope Mira3 LMU, Tescan. Methods of radiography determined that all synthesized nanostructured copper-zinc manganites crystallize in the cubic syngony with the following parameters of a lattice: LaMgCuZnMnO6 — а = 13.530.02 Å, Vo = 2476.810.06 Å3, Z = 4, Vo elect.cell = 619.200.02 Å3, roent = 4.52; pick = 4.500.01 g/cm3; LaCaCuZnMnO6 — а = 13.690.02 Å, Vo = 2565.730.06 Å3, Z = 4, Vo elect.cell. = 641.430.02 Å3, roent = 4.43; pick = 4.410.01 g/cm3; LaSrCuZnMnO6 — а = 13.910.02 Å, Vo = 2691.420.06 Å3, Z = 4, Vo elect.cell = 672.850.02 Å3, roent = 4.99; pick. = 4.960.01 g/cm3; LaBaCuZnMnO6 — а = 14.550.02 Å, Vo = 3080.270.06 Å3, Z = 4, Vo elect.cell = 770.070.02 Å3, roent = 4.95; pick = 4.940.01 g/cm3. The X-ray investigations demonstrated that the values of lattice parameters of the studied copper-zinc manganites have been increased from Mg to Ba. As a result of the investigations, these compounds can be included in Pm3m spatial group.
Исабаева LaMeIICuZnMnO6 (MeII — Mg, Ca, Sr, Ba) жаңа наноқұрылымды манганиттері
Новые наноструктурированные манганиты LaMeIICuZnMnO6 (MeII — Mg, Ca, Sr, Ba)
Keywords: synthesis; copper-zinc manganite; anthanum; alkaline-earth metals; nanostructured particles; electron microscopy; radiography